Technique comparison of pool and flume swimming - Wilson, B.; Takagi, H.; Pease, D. (coachesinfo.com, 1999)
Summary Many times research conducted in a flume is suspect since it is uncertain if swimmers swim the same way in a flume as they do in the pool. Typically swimmers not used to flume swimming experience apprehension the first couple of times in the flume. This potentially could lead to stroke mechanics from what is seen in the pool. This study was undertaken to compare stroke rates (SR) measured for freestyle swimming in a pool and a flume. SRs were monitored in fourteen males swimmers between 16 and 19 years of age while swimming in a flume and in a pool. Subjects performed a descending set of 6 x 50 meters on 5:00 ending with the subject's maximal effort. The same subjects were tested in the flume swimming at velocities starting at 0.8 meters/ second and increasing to the swimmer's fastest pace in increments of 0.2 meters/ second. Subjects were familiarized to flume swimming on the day prior to testing by performing several swims lasting approximately 30 minutes. Stroke rates were monitored for all swims. Statistical comparisons were made between flume and pool swimming. Results The results of the study showed that: Stroke rate changed significantly in both the pool and the flume as speed increased. Subjects showed higher stroke rates for the higher speeds. Significant differences in stroke rate were not seen between flume and pool swimming except at the highest velocity. Swimmers are able to adopt a swimming technique in the flume that models pool swimming. Implications These findings have several implications for swimming researchers and coaches. Based on stroke rates, it does not appear that flume swimming differs significantly from pool swimming, except at high velocities. And then the differences are extremely small. 30 minutes of swimming in the flume is enough to acclimatize a swimmer so they are able to mimic pool swimming. Research conducted in a flume, at least as it pertains to stroke rate, should be considered accurate. Results found from flume testing should accurately reflect pool swimming, provided swimmers have had an opportunity to warm up and feel comfortable in the flume. (In Biomechanics and Medicine in Swimming VIII. Keskinen, K., Komi, P and Hollander, P. (Eds). Jyvaskyla, Finland.)